Changes in sexual behavior patterns due to stimulants use: three case reports. Issue 3 (2nd April 2020) - Skryabin, Valentin Yurievich; Khoryaev, Denis; Torrado, Marco
Abstract: The paper describes three case reports of changes in sexual behavior patterns in male patients who use stimulants (amphetamine and mephedrone). Two of them demonstrate that the consumption of stimulants may lead to hypersexuality and excessive masturbation. Case report three shows that mephedrone use results in such typical stimulant-related subjective effects as the intensification of sensory experiences and sexual arousal. It leads to the loss of interest in sex without mephedrone. In light of the popularity of sex under the influence of drugs, clinicians should be aware of this phenomenon, since it is associated with high-risk sexual behavior. The description of clinical cases on the link between sex and drugs expands our knowledge in this area, leading to more effective treatment interventions.